Preparing a composite including SnS2, carbon nanotubes and S and using as cathode material of lithium-sulfur battery. (1st March 2020) - Jun, Wu; Bing, Chen; Qingqing, Liu; Ailin, Hu; Xiaoying, Lu; Qi, Jiang
Abstract: SnS2 is used to inhibit the "shuttle effect" and carbon nanotubes (CNTs) are used to improve the conductivity, thus a new Li-S battery cathode material (SnS2 /CNTs/S composite) is prepared in this paper. Morphological structure and electrochemical properties of the samples were characterized. The results show that among the composite, the CNTs are uniformly wrapped on the surface of SnS2 and S is uniformly loaded on the SnS2 /CNTs. The composite has a promising electrochemical performance: the first discharge capacity is 1308.6 mAh g  −   1 at 0.1 C and there is a reversible capacity of 1002.3 mAh g −1 after 100 cycles. Graphical abstract: A new SnS2 /CNTs/S composite is prepared and used as the lithium-sulfur battery cathode material. SnS2 works as the adsorbent to hinder or reduce the shuttle effect of lithium polysulfides. CNTs work as the conductive network of the composite. The synergistic effect come from the SnS2 and CNTs commits to the Li-S battery electrochemical performance. The composite has shown a good electrochemical performance. Image, graphical abstract